Root and tuber crops in Trinidad and Tobago - Seesahai, A. (International Center for Tropical Agriculture, 1986)
The supply and demand of root and tuber crops and their products in Trinidad and Tobago are analyzed; in this country, cassava and Colocasia esculenta var. esculenta are the main root crops grown. Aspects covered are characteristics of cultivated land, cropping systems, yields, socioeconomic profile of farmers, production vol., costs, and constraints, and marketing. Government policies on the importation of energy-rich agricultural products, domestic subsidies, import and export tariffs, credit, and production incentives are given. Regarding the future research on cassava, emphasis will be placed on the collection, multiplication, and selection of local and foreign germplasm and the introduction and agronomic evaluation of local and CIAT cv. Studies will be conducted on intercropping systems, CBB, storage systems, harvest mechanization, and physiological factors controlling yield. (CIAT)